Genre canon in the poem V.S. Vysotsky «Monument» - L S Shatalova (Polylinguality and Transcultural Practices, 2014)
The article considers the traditional Russian literature genre poems-monument, analyzes the features of this genre Canon, its components: the theme of the content, speech signals and compositional structure on the example of philological analysis of a poem by V.S. Vysotsky “Monument”.